2016
DOI: 10.18849/ve.v1i1.12
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence That Therapeutic Systemic Corticosteroid Administration is Associated With Laminitis in Adult Horses Without Underlying Endocrine or Severe Systemic Disease.

Abstract: Clinical bottom line There is currently no conclusive evidence to support a causal association between therapeutic systemic corticosteroid administration and the development of laminitis in healthy adult horses/ponies. There is weak evidence of an association between administration of multiple doses of systemic corticosteroid and the onset of laminitis in adult horses/ponies with underlying endocrine disorders or severe systemic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 18 publications
3
21
0
Order By: Relevance
“…25 If a horse developed laminitis ater 14 days, it was not included in the study as the time frame is too long to suggest a direct causal association. 4 The main limitation of this study was the lack of an untreated control population in study two. While comparisons can be made with other studies with similar populations of horses and study one, ideally, the study would have included a time-matched cohort of animals that was not treated with corticosteroids for a more appropriate comparison.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…25 If a horse developed laminitis ater 14 days, it was not included in the study as the time frame is too long to suggest a direct causal association. 4 The main limitation of this study was the lack of an untreated control population in study two. While comparisons can be made with other studies with similar populations of horses and study one, ideally, the study would have included a time-matched cohort of animals that was not treated with corticosteroids for a more appropriate comparison.…”
Section: Discussionmentioning
confidence: 93%
“…Since their introduction to veterinary therapeutics over 40 years ago, they have been associated with a perceived increased risk of acute laminitis. [1][2][3] However, there is little scientific evidence to support this association in healthy animals, 4 and direct causation has not been established. 5 There are several published case reports involving either single or small number of animals treated with corticosteroids that developed laminitis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous appraisals concluded that there was little or no evidence to indicate a significant risk of laminitis in a healthy adult horse or pony due to corticosteroid treatment but that there was weak evidence for increased risk in animals with pre‐existing risk factors (Menzies‐Gow ; McGowan et al . ). Recent UK evidence supports this conclusion assuming the healthy horse has no history of previous laminitis.…”
Section: Discussionmentioning
confidence: 97%
“…Many of the papers included in the recent appraisals (Menzies‐Gow ; McGowan et al . ) were retrieved and are not re‐appraised in this summary. The highest quality evidence retrieved was considered to be level 3 and 4 evidence.…”
Section: Search Outcomementioning
confidence: 99%
See 1 more Smart Citation